Decision Support System To Determine The Best Cafe Recommendations In Purwakarta Using MOORA Method - Dede Irmayanti; Ismi Kaniawulan; Mawar Wiliyanti (RISTEC : Research in Information Systems and Technology, 2024)
The growing cafe industry in Purwakarta presents challenges for customers in choosing the right cafe due to various factors such as distance, food prices, and service quality. This research aims to develop a Decision Support System using the MOORA method to efficiently recommend the best cafes based on predefined criteria. The research involved collecting data about cafes, analyzing the problem, and applying the MOORA method to rank cafes according to relevant criteria, such as distance, price, facilities, and service quality. The findings show that the MOORA method is effective in ranking cafés in Purwakarta, with cafés that get the highest score fulfilling the criteria of distance, price, facilities, and service quality, thus being recommended as the best choice for the community. This study concluded that the best café recommendation in Purwakarta is café salbeans park with the highest score of 0.093. In other words, café salbeans park is the best alternative. and it is recommended that this system be widely implemented and updated regularly to include the latest information about cafes, improving user experience in decision making.